Analysis of Gene Expression Profiles Regulating Phenotypic Transformation of Vascular Smooth Muscle Cells by Endothelial Cell-Derived Exosomes - Kang, T; Li, X; Hang, S; Lu, Y (Physiological research, 2025)
To establish a co-culture cell model and implement high-throughput gene sequencing of exosomes, we preliminarily demonstrated that endothelial cell-derived exosomes play a role in modulating the phenotypic transformation of vascular smooth muscle cells (VSMCs) by means of differentially expressed long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs). Primary rat aortic endothelial cells (ECs) and VSMCs were cultured for morphological observation, immunofluorescence (IF), and western blotting (WB). A co-culture model was established using a transwell system. A comparative analysis of ?-smooth muscle actin (?-SM actin), a marker of the contractile phenotype, and vimentin, indicative of the synthetic phenotype, was conducted to assess the expression levels in both co-culture and control setups. Isolated exosomes were obtained using an exosome-specific isolation kit, followed by detailed characterization using transmission electron microscopy (TEM) for morphological assessment, nanoparticle tracking analysis (NTA) for size distribution, and WB for protein profiling. Primary aortic ECs were isolated, cultured, and characterized. In the Transwell co-culture model, VSMCs transitioned to a contractile phenotype, exhibiting increased alpha-smooth muscle actin (?-SMA, contractile marker) and decreased Vimentin (synthetic marker). Exosomes were extracted, purified, and characterized by their morphology, diameter, concentration, and marker proteins (CD9, CD63, and CD81). RNA-seq and bioinformatic analyses were conducted on muscle cells before and after treatment. The Transwell-based ECs-VSMCs co-culture model significantly upregulates contractile phenotype protein expression in VSMCs, promoting their transition to a contractile state. Differentially expressed exosomal genes, including lncRNAs and circRNAs, modulate proliferation, differentiation, and phenotypic transformation of VSMCs.
Keywords: Myocytes, Smooth Muscle; transkriptom; Exosomes; Muscle, Smooth, Vascular; fenotyp; Male; Phenotype; Endothelial Cells; endoteliální buňky; potkani Sprague-Dawley; RNA, Circular; Transcriptome; exozómy; mužské pohlaví; stanovení celkové genové exprese; Coculture Techniques; Gene Expression Profiling; krysa rodu Rattus; kultivované buňky; Animals; svaly hladké cévní; zvířata; kruhová RNA; Rats; kokultivační techniky; Cells, Cultured; myocyty hladké svaloviny; Rats, Sprague-Dawley